Enhancing hospital pharmacy attachment: integrating simulation labs for future pharmacists / Nor Elyzatul Akma Hamdan - Hamdan, Nor Elyzatul Akma (Faculty of Pharmacy, 2025)
From December 9th, 2024, to January 10th, 2025, the Hospital Pharmacy Attachment (HPA) was conducted at the Pharmacy Department of Hospital Al Sultan Abdullah, and Faculty of Pharmacy, Universiti Teknologi MARA (UiTM). This programme is designed to equip future pharmacists with essential practical skills and knowledge through structured experiential training. This structured experiential training, offered during the final year of the Bachelor of Pharmacy programme, spans four weeks and is a compulsory part of the curriculum.